Intracisternal delivery of PEG-coated gold nanoparticles results in high brain penetrance and long-lasting stability - Antonello Spinelli; Maria Girelli; Daniela Arosio; Laura Polito; Paola Podini; Gianvito Martino; Pierfausto Seneci; Luca Muzio; Andrea Menegon (Journal of Nanobiotechnology, 2019)
Abstract Background The increasing use of gold nanoparticles (AuNPs) in the field of neuroscience instilled hope for their rapid translation to the clinical practice. AuNPs can be engineered to carry therapeutics or diagnostics in the diseased brain, possibly providing greater cell specificity and low toxicity. Although there is a general enthusiasm for these tools, we are in early stages of their development. Overall, their brain penetrance, stability and cell specificity are critical issues that must be addressed to drive AuNPs to the clinic. Results We studied the kinetic, distribution and stability of PEG-coated AuNPs in mice receiving a single injection into the cisterna magna of the 4th ventricle. AuNPs were conjugated with the fluorescent tag Cy5.5 (Cy5.5-AuNPs) to track their in vivo distribution. Fluorescence levels from such particles were detected in mice for weeks. In situ analysis of brains by immunofluorescence and electron microscopy revealed that Cy5.5-AuNPs penetrated the brain parenchyma, spreading in the CNS parenchyma beneath the 4th ventricle. Cy5.5-AuNPs were preferentially found in neurons, although a subset of resting microglia also entrapped these particles. Conclusions Our results suggest that the ICM route for delivering gold particles allows the targeting of neurons. This approach might be pursued to carry therapeutics or diagnostics inside a diseased brain with a surgical procedure that is largely used in gene therapy approaches. Furthermore, this approach could be used for radiotherapy, enhancing the agent’s efficacy to kill brain cancer cells.